PERSPEKTIF HINDU DHARMA TERHADAP PRINSIP-PRINSIP PERLINDUNGAN KEMANUSIAAN DALAM HUKUM HUMANITER INTERNASIONAL - Suastana, I Made Dwija (VYAVAHARA DUTA, 2026)
The relationship between Hindu Dharma values and humanitarian protection principles inInternational Humanitarian Law (IHL) is an intellectual article that needs a comprehensiveresearch. IHL aims to safeguard human dignity during armed conflicts, which aligns with HinduDharma teachings on dharma, ahimsa (non-violence), and respect for life. Classical Hindu texts,such as the Mahābhārata, Bhagavadgītā, and Manu Dharmaśāstra, emphasize ethics of war(dharma yuddha), prisoner protection, and violence limitation. Modern case studies, includingthe Gaza-Israel conflict (2023–2025), reveal ongoing violations of IHL. This analysisdemonstrates that integrating Hindu Dharma values with IHL principles can strengthen theethical foundation of humanitarian law implementation in the contemporary era.Keywords: Hindu Dharma, International Humanitarian Law, Ahimsa, Dharma Yuddha, ManuDharmaśāstra, Humanitarian Protection